2010
DOI: 10.1111/j.1741-3737.2010.00732.x
|View full text |Cite
|
Sign up to set email alerts
|

Religion in Families, 1999–2009: A Relational Spirituality Framework

Abstract: This review examines the role of religion, for better and worse, in marital and parent-child relationships according to peer reviewed studies from 1999–2009. A conceptual framework labeled “relational spirituality” is used to: (a) organize the breadth of findings into the three stages of the formation, maintenance, and transformation of family relationships, and (b) illustrate three in-depth sets of mechanisms to delve into unique ways religion may shape family bonds. Topics include union formation, fertility,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
568
5
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 423 publications
(601 citation statements)
references
References 96 publications
(143 reference statements)
24
568
5
4
Order By: Relevance
“…Past studies state that partner religiosity contributes to relationship quality (e.g., Clements et al 2004), whereas other studies illustrate that partner religiosity does not influence relationship quality (e.g., Mahoney 2010). Although these studies focus on married couples, results of the current study illustrate the importance for dating couples to participate in religious activities together, rather than one of the coupled participants participating in religious activities.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Past studies state that partner religiosity contributes to relationship quality (e.g., Clements et al 2004), whereas other studies illustrate that partner religiosity does not influence relationship quality (e.g., Mahoney 2010). Although these studies focus on married couples, results of the current study illustrate the importance for dating couples to participate in religious activities together, rather than one of the coupled participants participating in religious activities.…”
Section: Discussionmentioning
confidence: 54%
“…However, research on the influence of partner religiosity for relationship quality have produced mixed results. While some studies demonstrated that partners' religiosity was positively associated with relationship quality (Clements et al 2004;Perry 2015), other studies displayed no significant effects of partner religiosity for relationship quality (Mahoney 2010;Mahoney et al 2001). Gender appears to provide an explanation for this discrepancy, as some studies illustrated that women benefited more from having religious partners than men who have religious partners (Lopez et al 2011).…”
Section: Religiosity and Romantic Relationshipsmentioning
confidence: 99%
“…This paper answers the call of religion and family scholars who have urged researchers to examine more thoroughly the role of religion on families of the various minority religious traditions (i.e., non-Christian), and to rely more on qualitative data [1,5,13]. The purpose of this paper is to examine the role of Islam on marital and familial relationships and to present our participants' reflections on sensitive issues, including gender roles, women's rights and marital unity.…”
Section: Introductionmentioning
confidence: 83%
“…After analyzing 184 studies (1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)) on various connections between religion and family life, Mahoney suggested that researchers must narrow their foci as they move forward [5]. Specifically, for example, she identified a need to examine nontraditional families, religious and ethnic minority families and to use more qualitative and high-quality quantitative (e.g., longitudinal) methods.…”
Section: Overview Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation